Digital divide, craft firms' websites and urban-rural disparities—empirical evidence from a~web-scraping approach - Anita Thonipara; Rolf Sternberg; Till Proeger; Lukas Haefner (Review of Regional Research, 2022)
Following the "death of distance" postulate, digitalization may reduce or even eliminate the penalty of firms being located in rural areas compared with those in urban agglomerations. Despite many recent attempts to measure digitalization effects across space, there remains a~lack of empirical evidence regarding the adoption of digital technologies from an explicit spatial perspective. Using web-scraping data for a~sample of 345,000 small firms in Germany, we analyze the determinants of website prevalence. Comparing urban with rural areas, we show that running a~website—as a~proxy for the degree of digitalization of the respective firm—is highly dependent on location, whereby firms in urban areas are almost twice as likely to run websites compared with those located in rural areas. Our county-level analysis shows that a~high population density, a~young population and a~high educational level have a~positive and significant association with the probability that firms run websites. Surprisingly, we find a~negative and significant association of gross domestic product per capita with website prevalence, which is driven by urban regions. There are no differences between urban, semi-urban and rural areas in terms of website up-to-dateness as well as social media prevalence. We conclude that there is a~substantial digital divide and discuss policy implications.Dem Postulat des "Endes der Entfernung" zufolge kann die Digitalisierung die Nachteile für Unternehmen in ländlichen Gebieten gegenüber Unternehmen in städtischen Ballungsräumen verringern oder sogar beseitigen. Doch trotz einiger jüngerer Versuche räumliche Digitalisierungseffekte zu messen, besteht nach wie vor ein Mangel an empirischer Evidenz bezüglich der Nutzung digitaler Technologien aus einer räumlichen Perspektive. Mithilfe einer Web-Scraping Analyse untersuchen wir die Determinanten der Verbreitung von Websites für 345.000 kleine Unternehmen aus Deutschland. Der Vergleich städtischer und ländlicher Regionen zeigt, dass das Betreiben einer Website, als Näherungswert für das Digitalisierungsniveau eines Unternehmens, stark von dessen Standort abhängt. Unternehmen in Städten betreiben fast doppelt so häufig eine Website wie Unternehmen in ländlichen Regionen. Unsere Analyse auf der Kreisebene zeigt, dass eine hohe Bevölkerungsdichte, eine junge Bevölkerung und ein hohes Bildungsniveau einen positiven und signifikanten Zusammenhang aufweist mit der Wahrscheinlichkeit, dass ein Unternehmen eine Website betreibt. Überraschenderweise finden wir einen negativen und signifikanten Zusammenhang zwschen dem Bruttoinlandsprodukt pro Person mit der regionalen Verbreitung von Websites. Dieses Ergebnis wird maßgeblich durch städtische Regionen bestimmt. Wir finden keine Unterschiede zwischen städtischen, semi-urbanen und ländlichen Regionen bezüglich der Aktualität sowie der Verbreitung von Social Media. Wir folgern, dass es einen erheblichen digital divide gibt und stellen Ansätze für politische Maßnahmen vor.
Keywords: 910; Digital divide; Digitalization; Rural; Small and Medium-Sized Enterprises; Urban; Web-scraping